The Roles of Cognitive Styles and Emotional Intelligence on Job Performance - Alimat Jumoke, Lamina; Sopian, Bujang; Jibril Adewale, Bamgbade (Human Resource Management Academic Research Society, 2023)
Over the years, construction scholars have identified the essence of professionals' cognitive styles and emotional intelligence in project delivery. This study contributes to the ongoing discussion on the construction stakeholders' job performance by identifying the direct and indirect influence of cognitive styles (knowing, planning, and creating styles) and underlying emotional intelligence dimensions (self-emotional appraisal, use of emotion, regulation of emotion and other's emotional appraisal) on construction professionals' job performance. Using survey data from Sarawak construction consultants, the population stood at 311, while 180 were sampled for this study. Structural equation modelling (SEM) was used to confirm the underpinning cognitive-motivational relational theory (CMRT) and the role of cognitive styles in emotional intelligence and job performance link. The findings demonstrated the mediating role of cognitive styles on the emotional intelligence and job performance relationship. The limitations and future research directions are also discussed.